Impact of bone marker feedback on adherence to once monthly ibandronate for osteoporosis among Asian postmenopausal women - Annie Wai Chee Kung (2018)
Aim: his study assesses the impact of serum carboxy-terminal collagen crosslinks (CTX) bone marker feedback (BMF) on adherence to ibandronate treatment in Asian postmenopausal women with osteoporosis. Methods: This was a 12-month (6-monthly phased), randomized, prospective, open-label, multi-center study conducted in 596 (of 628 enrolled) postmenopausal women with osteoporosis (≤ 85 years old) who were naïve, lapsed, or current bisphosphonate users. Patients were randomized into two arms: serum CTX BMF at 3 months versus no-BMF. Once-monthly 150 mg ibandronate tablet was administered for 12 months and adherence to therapy was assessed at 6 and 12 months. In addition, patient satisfaction and safety of ibandronate treatment were also assessed. Results: Serum CTX BMF at 3 months showed no impact on adherence. The proportions of adherent patients were comparable in the BMF versus no-BMF arms (92.6% vs. 96.0%, P = 0.16); overall, serum CTX levels were similar for adherent and non-adherent patients. However, BMF patients felt more informed about their osteoporosis (P < 0.001) and more satisfied (P < 0.01) than no-BMF patients. Conclusions: The Asian postmenopausal osteoporosis patients in this study had a high adherence rate to once-monthly ibandronate therapy. Use of serum CTX BMF had no further impact on increasing adherence, but increased treatment satisfaction. © 2009 Asia Pacific League of Associations for Rheumatology and Blackwell Publishing Asia Pty Ltd.